Sharp interfaces in p+-AlGaAs/n-GaAs epitaxial structures obtained by MOCVD - Vakiv, N. M.; Krukovskii, S. I.; Larkin, S. Yu.; Avksent'ev, A. Yu.; Krukovskii, R. S. (Technology and design in electronic equipment, 2014)
The complexity of forming sharp and high-quality boundaries in p+AlGaAs/n-GaAs systems by MOCVD method is caused by differing on 80–120°С optimal crystallization temperature of GaAs layers and n-AlGaAs solid solutions. A method of forming qualitative hetero boundaries under conditions of continuous growth at changing crystallization temperature from 600–700°C has been developed. It has been determined that the crystallization of p+-AlGaAs: Zn solid solution layer on the surface of n-GaAs:Si layer, with increasing the crystallization temperature in the temperature range of 600–760°C at a rate 8–10 °C/min allows to crystallize sharp impurity boundary between the layers of p- and n-type conductivity. The method of forming sharp hetero boundaries in p-GaAs:Zn/n-GaAs:Si systems can be used for manufacturing wide range of epitaxial structures.